Periodontitis - A Hidden Danger: Causes, Symptoms and Prevention (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article provides detailed information about periodontitis, its causes, symptoms and complications. Also, special attention is paid to early detection of the disease, methods of treatment and preventive measures. The article covers recommendations of dentists and important aspects of maintaining oral hygiene. The effect of periodontitis on general health is also considered, and useful tips for patients are given. This article may be useful for medical professionals, dentists and the general public.